Expend, a Gauss programme for non-linear GMM estimation of exponential models with endogenous regressors for cross section and panel data - Frank Windmeijer (Centre for Microdata Methods and Practice (cemmap), 2002)
ExpEnd is a Gauss programme for non-linear generalised method of moments (GMM) estimation of exponential models with endogenous regressors for cross section and panel data. The estimators included in this package are simple Poisson pseudo ML; GMM for cross section data using moment conditions based on multiplicative or additive errors; within groups fixed effects Poisson for panel data; GMM estimation using quasi-differenced moment conditions eliminating unobserved heterogeneity and allowing for predetermined or endogenous regressors; and quasi-differenced GMM for a dynamic linear feedback model. This manual describes in detail the various estimators, the data and software requirements, and the programme commands.
Keywords: C13; C21; C23; 330; Generalised Method of Moments; Count Data; Panel data; Panel; Theorie; Nichtlineares Verfahren; Momentenmethode